2018
DOI: 10.1177/000313481808401137
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Wound Coverage Techniques in Extremity Necrotizing Soft Tissue Infections

Abstract: Little data exist about management of wounds created by debridement in necrotizing soft tissue infections (NSTIs). Multiple wound coverage techniques exist, including complete primary wound closure, split-thickness skin grafting, secondary intention, and flap creation. We hypothesized that all wound coverage techniques would be associated with high rates of successful wound coverage and low crossover rates to other wound coverage techniques. NSTIs over a three-year period were retrospectively reviewed. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The cutoff ratio deeming the success or failure of skin graft take is not consensual. It depends on intrinsic and extrinsic factors (such as the location, thickness, or type/etiology of the defect) and varies from 50% to 90% in the literature ( Birchall et al, 1991 ; Kirsner et al, 1995 ; Thourani et al, 2003 ; Shores et al, 2012 ; Reddy et al, 2014 ; Lauerman et al, 2018 ; Braza and Fahrenkopf, 2022 ). In clinical applications of skin grafts, we consider an engraftment of over 80% of the graft area on days 15–21 as successful since the patient does not require additional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff ratio deeming the success or failure of skin graft take is not consensual. It depends on intrinsic and extrinsic factors (such as the location, thickness, or type/etiology of the defect) and varies from 50% to 90% in the literature ( Birchall et al, 1991 ; Kirsner et al, 1995 ; Thourani et al, 2003 ; Shores et al, 2012 ; Reddy et al, 2014 ; Lauerman et al, 2018 ; Braza and Fahrenkopf, 2022 ). In clinical applications of skin grafts, we consider an engraftment of over 80% of the graft area on days 15–21 as successful since the patient does not require additional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A study in 46 NSTI patients concluded that reconstruction with STSG was best. 13 While STSG may be the most viable option, drawbacks include an additional wound, pain management, and significant scarring limiting functionality as well as poor cosmetic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure results in a second painful wound that may take more time for healing than the graft site itself [4]. Such wound also carries the risk of some complications like infection, hyper or hypo pigmentation, burning sensation, itching and even excessive scarring that may minimize the range of motion [2]. The split-thickness skin graft is a weak coverage that may ulcerate if exposed to mechanical forces, also it may adhere to the underlying structures [5,6] in addition to limited donor site availability in major burns [7].…”
Section: Introductionmentioning
confidence: 99%